Consequence of Ayurveda Remedies with Diet and Life Style in the Male Infertility: A Critical Review. - Nayak, Sourav; Varsakiya, Jitendra (International Research Journal of Ayurveda & Yoga, 2024)
Background: Infertility is a major medico-social issue now a days. The absence of conception after a year of sexual activity without the use of contraception is known as infertility. Every sixth couple has infertility at some point in their relationship.80 million people worldwide experience pregnancy failure, according to reports from the World Health Organization. About After a year, 15% of couples are still unable to conceive. The prevalence of male infertility is 7%. Idiopathic male infertility occurs when aberrant semen parameters are found because of unknown causes. Oligozoospermia is a condition when a man’s sperm count in his semen is below 15 million/ml. In classics, the situations described under Kheena Shukra -vitiation of Shukra Dhatu by Vata and Pitta Dosha. Aims: To review Ayurvedic aspect of Ksheena Shukra and male infertility with details management. Materials and methods: Relevant Ayurveda and modern literature available information on web sources searched to fulfill the Aim.: Discussion: The majority of patients use assisted reproductive technologies or intrauterine insemination to become fertile. Unfortunately, success rates are minimal in situations where the sperm count is extremely low. It’s time to investigate reproductive aids derived from herbal, herbo-mineral formulations with regard to healthy lifestyle and diet management. Conclusion: Current article reviles the details management and scope of Ayurveda in the field of andrology.